Trends in personalized nutrition - Galanakis, Charis M. (Academic Press, an imprint of Elsevier, 2019)
Trends in Personalized Nutrition explores the topic of personalized nutrition from multiple angles, addressing everything from consumer acceptance, to policies and cognitive dissonance. Sections in the book cover epigenetics, nutrigenomics, predicting glycemic response, and metabolomics and the role of bacteria. In addition, the book explores diet, obesity and personalized nutrition for athletes, women, and infants and children, along with a section on the role of modern technology in the promotion of personalized nutrition. Nutritionists, food technologists, food chemists, new product developers, academics, and researchers and physicians working in the field of nutrition will find this to be a great reference.